2014
DOI: 10.1097/aog.0000000000000049
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Vitamin D Status and Small-for-Gestational-Age Offspring in Women at High Risk for Preeclampsia

Abstract: Objective To examine the association between second-trimester maternal serum 25-hydroxyvitamin D (25[OH]D) concentrations and risk of small for gestational age (SGA) in singleton, live births. Methods We assayed serum samples at 12 to 26 weeks of gestation for 25(OH)D in a sample of participants in a multicenter clinical trial of low-dose aspirin for the prevention of preeclampsia in high-risk women (n=792). Multivariable log-binomial regression models were used to assess the association between 25(OH)D and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
58
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 45 publications
6
58
1
Order By: Relevance
“…Vitamin D deficiency in pregnancy is associated to fetal growth restriction (FGR) (Gernand et al, 2014; Gernand et al, 2013), however the underlying mechanisms remain unknown. In the current study, we demonstrate for the first time that 1,25-dihydroxy vitamin D 3 promotes amino acid transport in cultured PHT cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D deficiency in pregnancy is associated to fetal growth restriction (FGR) (Gernand et al, 2014; Gernand et al, 2013), however the underlying mechanisms remain unknown. In the current study, we demonstrate for the first time that 1,25-dihydroxy vitamin D 3 promotes amino acid transport in cultured PHT cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, the incidence of vitamin D deficiency continues to rise and women of reproductive age are particularly at risk of deficiency (Looker et al, 2011). Besides the well-established function of vitamin D in calcium homeostasis and bone mineralization, vitamin D deficiency during pregnancy is associated with a range of poor perinatal outcomes, including preterm birth, pre-eclampsia, small-for-gestational-age infants, insulin resistance and gestational diabetes mellitus (Bodnar et al, 2014; Gernand et al, 2014). The mechanisms underlying these associations are not fully understood, however the placenta, which is the interface between maternal and fetal circulations, is likely to be involved.…”
Section: Introductionmentioning
confidence: 99%
“…Bener A et al studied that hypovitaminosis D was associated with 5 times higher chance of developing hypertension during pregnancy [5].The risk of the mothers giving birth to neonates which were small for gestation age was also much higher when they had suboptimal Vitamin D levels [6]. Vitamin D has a regulatory action on centrally acting vasodilating agents and has been found to regulate blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…They all arrived at similar conclusions wherein they observed that suboptimal Vitamin D in mothers can lead to gestational diabetes mellitus, various forms of hypertensive disorders of pregnancy and pregnancy induced anaemia[19,2,20,21,5,6]. Aghajafari et al (2009) and Gernand et al (2014)studied the neonatal outcomes along with the maternal complications and concluded that maternal Vitamin D deficiency had a higher risk of preterm infants and babies which were small for the gestational age (SGA)[20,6].Robinson et al (2010) andBodnar et al (2014) noted that their cases with severe preeclampsia were associated with extremely low levels of vitamin D.…”
mentioning
confidence: 99%
“…With respect to foetal growth, maternal pre-natal vitamin D deficiency has been associated with lower birth weight and an increased risk of babies born small for gestational age (SGA; weight <10th percentile for gestational age) (Leffelaar et al, 2010; Aghajafari et al, 2013; Gernand et al, 2013, 2014). A Cochrane review of pre-natal vitamin D supplementation trials reported a tendency for supplemented women to be less likely to give birth to babies with low birth weight (LBW; <2500 g), although statistical significance was borderline (De-Regil et al, 2012).…”
Section: Introductionmentioning
confidence: 99%